2021
DOI: 10.3390/en14133878
|View full text |Cite
|
Sign up to set email alerts
|

Energy Intensity Reduction in Large-Scale Non-Residential Buildings by Dynamic Control of HVAC with Heat Pumps

Abstract: One of the main elements for increasing energy efficiency in large-scale buildings is identified in the correct management and control of the Heating Ventilation and Air Conditioning (HVAC) systems, particularly those with Heat Pumps (HPs). The present study aimed to evaluate the perspective of energy savings achievable with the implementation of an optimal control of the HVAC with HPs. The proposed measures involve the use of a variable air volume system, demand-controlled ventilation, an energy-aware control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
(46 reference statements)
0
8
0
1
Order By: Relevance
“…Besarnya energi yang dibutuhkan menjadikan sistem pengondisi udara sebagai objek pengubahsuaian yang signifikan, maka dari itu diperlukan inovasi dan penyesuaian sistem pengondisi udara agar sesuai dengan prinsip berkelanjutan, yang sekaligus dapat mengurangi konsumsi energi dan biaya. Dalam penelitian yang dilakukan oleh Franco [14] dengan menggunakan Heat Pump Elektrik dan Demand Controller Ventillation pada sistem HVAC didapat penghematan energi sebesar 75% dibandingkan dengan sistem HVAC konvensional.…”
Section: Analisis Regresi Linear I Uji Multikolinearitasunclassified
“…Besarnya energi yang dibutuhkan menjadikan sistem pengondisi udara sebagai objek pengubahsuaian yang signifikan, maka dari itu diperlukan inovasi dan penyesuaian sistem pengondisi udara agar sesuai dengan prinsip berkelanjutan, yang sekaligus dapat mengurangi konsumsi energi dan biaya. Dalam penelitian yang dilakukan oleh Franco [14] dengan menggunakan Heat Pump Elektrik dan Demand Controller Ventillation pada sistem HVAC didapat penghematan energi sebesar 75% dibandingkan dengan sistem HVAC konvensional.…”
Section: Analisis Regresi Linear I Uji Multikolinearitasunclassified
“…The HVAC system consists of an Air Handling Unit (AHU) equipped with a plate heat exchanger for Heat Recovery (HR), a mixing chamber, a preheat, cooling and dehumidification, and reheat coil heat exchangers, an adiabatic humidifier, a chiller, a boiler or an air-to-water heat pump, and fans. The model has been extensively described in recent papers by the authors, as [9,18], and its representation in the baseline configuration involving the boiler, a hydraulic scheme and constant flow rate fans is presented in Figure 2. The building energy demands are used to evaluate the air supply flow rate, tempe ature, and humidity ratio to guarantee the exact balance between the energy required an the energy delivered based on the control strategy involved: the values depend on th considered ventilation technique, since CAVs operate at a constant flow rate while VAV The building energy demands are used to evaluate the air supply flow rate, temperature, and humidity ratio to guarantee the exact balance between the energy required and the energy delivered based on the control strategy involved: the values depend on the considered ventilation technique, since CAVs operate at a constant flow rate while VAVs modulate it according to the needs.…”
Section: Hvac System Modelmentioning
confidence: 99%
“…In this study, we explore HVAC operational characteristics and associated savings through the analysis of buildings for educational purposes. In a previous paper [18], the authors have shown how a significant energy consumption reduction, of about 80%, can be achieved in a large academic building with the use of electrically driven heat pumps (HPs), of Variable Air Volume (VAV) systems, and of Demand Controlled Ventilation (DCV), compared to a benchmark solution involving the use of fossil fuels and a Constant Air Volume (CAV) system. This has led to the identification of a fossil-fuel-free generation and an occupancy-aware ventilation as the possible keys to improve the energy management in the building sector on full scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, a common consensus in the research community regarding gaps in this field is the lack of demonstrations that implement MPC on heat-pump systems with off-the-shelf components and compare its performance with conventional controllers under almost-identical conditions [5,15,16]. The technical challenges in deploying such optimization-based energy plant management systems are firstly the inclusion of the operational restrictions of these components and secondly the integration of the controller in existing building automation and control (BAC) frameworks.…”
Section: Introductionmentioning
confidence: 99%